Implementasi Akuntabilitas Manajemen Berbasis Sekolah Dalam Pengelolaan Keuangan Di SD Negeri 1 Tanjung - Nabilatus Sofi; Mauritsa Akmalia Khoirun Niam; Muhimmatul Zulfa Assa’adah; Diana Sukma Az Zahra; Devi Apriliya Putri; Wahyu Widdiya Sari; Nur Rohman (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
School financial management is a vital component in supporting the effectiveness and quality of education. However, the implementation of accountability principles at the elementary level often faces various challenges, such as limited administrative skills, lack of transparency, and low stakeholder participation. This study aims to examine the implementation of accountability principles within the framework of School-Based Management (SBM) in managing school finances at SD Negeri 1 Tanjung, Jepara. Using a qualitative descriptive approach with a case study design, data were collected through semi-structured interviews, non-participant observations, and documentation. Research subjects included the principal, treasurer, teachers, and school committee. The data were analyzed using the interactive model of Miles and Huberman, and data validity was ensured through triangulation of sources and methods. The results show that the school has applied several accountability procedures, including participatory planning through RKAS, digital financial reporting via ARKAS, and public transparency efforts such as financial disclosures in meetings and notice boards. Nonetheless, the school still encounters challenges such as delayed government funding disbursements, limited financial administration skills, and passive community involvement. This study provides valuable insights for improving financial governance in schools by recommending regular capacity-building training, the use of user-friendly digital systems, and increased community participation in financial oversight. The findings are expected to serve as a reference for similar schools and inform local education authorities in developing more accountable school financial management practices.